2020
DOI: 10.3390/cryst10110978
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids/Deep Eutectic Solvents-Based Hybrid Solvents for CO2 Capture

Abstract: The CO2 solubilities (including CO2 Henry’s constants) and viscosities in ionic liquids (ILs)/deep eutectic solvents (DESs)-based hybrid solvents were comprehensively collected and summarized. The literature survey results of CO2 solubility illustrated that the addition of hybrid solvents to ILs/DESs can significantly enhance the CO2 solubility, and some of the ILs-based hybrid solvents are super to DESs-based hybrid solvents. The best hybrid solvents of IL–H2O, IL–organic, IL–amine, DES–H2O, and DES–organic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Jiang et al 57 considered DBN:2imidazolidone, or DBN:1,3-dimethylurea or DBN:dimethylurea DESs, also reporting an improvement of capturing ability, especially for 2-imidazolidone. Additional relevant studies considering superbases were reported by Zhang et al 58 (considering DBN) and Yan et al 59 (considering DBU in superbase ILs mixed with ethylene glycol for DES development) showing in all the cases reversible and efficient CO 2 adsorption, as confirmed by the analysis reported by Liu et al 60 Nevertheless, these superbase-based DESs systems may present problems related to the increase of viscosity upon CO 2 capture, the poor performance of desorption cycles, with only 23% release of captured CO 2 upon heating to 60 °C. 56 Similarly, that of superbase−DESs has been questioned in the literature, 61 considering the poor thermals stability of superbases in certain solvents, as well as the extreme sensitivity of superbases toward water, 62 which would require special conditions from their preparation and handling hindering scaling up.…”
Section: Des Utilization In Challenging Energy and Fuels Processessupporting
confidence: 67%
“…Jiang et al 57 considered DBN:2imidazolidone, or DBN:1,3-dimethylurea or DBN:dimethylurea DESs, also reporting an improvement of capturing ability, especially for 2-imidazolidone. Additional relevant studies considering superbases were reported by Zhang et al 58 (considering DBN) and Yan et al 59 (considering DBU in superbase ILs mixed with ethylene glycol for DES development) showing in all the cases reversible and efficient CO 2 adsorption, as confirmed by the analysis reported by Liu et al 60 Nevertheless, these superbase-based DESs systems may present problems related to the increase of viscosity upon CO 2 capture, the poor performance of desorption cycles, with only 23% release of captured CO 2 upon heating to 60 °C. 56 Similarly, that of superbase−DESs has been questioned in the literature, 61 considering the poor thermals stability of superbases in certain solvents, as well as the extreme sensitivity of superbases toward water, 62 which would require special conditions from their preparation and handling hindering scaling up.…”
Section: Des Utilization In Challenging Energy and Fuels Processessupporting
confidence: 67%
“…Also, HIF was successfully dissolved in 5 wt % of microcrystalline cellulose . Afterwards, in a review compiled by Liu et al, the solubilities and viscosities of CO 2 in HIFs were compared with those of ILs and DESs; the results indicated that HIF-based solvents are excellent candidates for CO 2 capture . Also, Xu et al utilized the combination of the DES choline chloride/ethylene glycol (ChCl/EG) and the ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate (C 4 MIM·PF 6 ) to improve the biocatalytic reduction of 2-octanone with Acetobacter pasteurianus GIM1.158 cells; the study concluded that the combination (DES + IL) possessed good biocompatibility with the cells and acted as a good substrate reservoir .…”
Section: Introductionmentioning
confidence: 99%
“…In this project, MEA and tetrabutylphosphonium methanesulfonate ([TBP][MeSO 3 ]) were selected to be mixed, producing aqueous hybrid solvent for CO 2 removal. The MEA concentration was kept constant at 30 wt% as per typical amine concentrations used in commercialized CO 2 absorption technology [13,14]. The selection of [TBP][MeSO 3 ] was based on the results of a screening study using the Conductor-like Screening Model for Real Solvents (COSMO-RS) by Azman [15].…”
Section: Introductionmentioning
confidence: 99%